Predictive Value of Estimated Glomerular Filtration Rate for the Prognosis of Elderly Patients With Acute Myocardial Infarction - Namkyun Kim; Hun Sik Park; Jae Yong Yoon; Hyun Jun Cho; Chang-Yeon Kim; Jae-Hyung Roh; Myung Hwan Bae; Jang Hoon Lee; Dong Heon Yang; Yongkeun Cho; Shung Chull Chae; Jihyun Sohn; et al. (Annals of Geriatric Medicine and Research, 2017)
Background : The aim of this study was to investigate the predictive value of estimated glomerular filtration rate (eGFR) calculated with the simplified Modification of Diet in Renal Disease (MDRD) Study and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations for prognosis in elderly patients with acute myocardial infarction (AMI). Methods : This study included 1,372 patients (mean age, 64.2±11.8 years; men, 67.9%) entered in the Kyungpook National University Hospital Acute Myocardial Infarction Registry from November 2005 to February 2010. We analyzed 1-year major adverse cardiac events (MACE) according to the eGFR calculated with the simplified MDRD Study and CKD-EPI equations. Results : The mean eGFR values calculated with the MDRD Study and CKD-EPI equations were 81.3±44.4 and 78.5±27.1 mL/(min/1.73 m²), respectively. In receiver operating characteristic curve analysis for prediction of 1-year MACE, the area under the curve based on the CKD-EPI equation was greater than that using the MDRD Study equation (CKD-EPI equation vs. MDRD Study equation: 0.691 vs. 0.674, p=0.041). Multivariate analysis using a Cox proportional hazards model revealed that the eGFR calculated with the CKD-EPI equation was an independent predictor of the occurrence of MACE within 1 year after AMI. However, eGFR calculated with the MDRD Study equation did not have predictive value. Furthermore, the eGFR calculated with the CKD-EPI equation had incremental prognostic value for established risk factors (chi-square=5.78, p=0.016). Conclusion : The eGFR calculated using the CKD-EPI equation was an independent predictor of 1-year MACE in elderly patients with AMI.